Back to School Special: “The Top Ten Most Viewed” and More - EAA Editorial Office (Education About Asia, 2021)
the EAA “most viewed” list indicates the top ten most viewed articles in a given week. Several articles have remained high on the list for long periods of time, but there is enough movement up, down, or off the list that checking it regularly remains interesting. The articles below from our top ten most viewed rankings were taken on August 26th, 2022.
Keywords: Asia General; China; China and Inner Asia; East Asia; India; Indonesia; Japan; Korea; Northeast Asia; Philippines; South Asia; Southeast Asia